Perancangan Sistem Pakar Diagnosa Penyakit Pada Tyto Alba Berbasis Web (Information Technology and Telematics, 2015)
ABSTRACT Understanding of the disease in the Tyto Alba is still low. Lots of people still rely on the expertise of experts manually. So that the costs to society are quite expensive and the views from the time also less efficient. Media consultation is the application of computer-based expert system that uses facts and reasoning techniques in solving a problem that usually can only be solved by an expert in a particular field. Application of Expert System produces an application program that can be used to diagnose the possibility of disease in birds Tyto Alba based on symptoms suffered by the user. This application uses the certainty factor method implementation using the programming language PHP and MySQL supporting data storage. In this application will display the symptoms of each disease. The final result of applications such as the type of disease symptoms were selected based on the input. Keywords: expert system, diseases Tyto Alba, certainty facto ABTRAKSI Pemahaman masyarakat akan penyakit pada Tyto Alba masih rendah. Banyak sekali masyarakat masih mengandalkan keahlian dari pakar secara manual. Sehingga biaya yang ditanggung masyarakat cukup mahal dan dilihat dari waktu juga kurang efisien. Media konsultasi ini merupakan aplikasi dari Sistem Pakar berbasis komputer yang menggunakan fakta dan tehnik penalaran dalam memecahkan masalah yang biasanya hanya dapat dipecahkan oleh seorang pakar dalam bidang tertentu. Aplikasi Sistem Pakar ini menghasilkan program aplikasi yang dapat digunakan untuk mendiagnosa kemungkinan penyakit pada burung Tyto Alba berdasarkan gejala yang diderita oleh user. Aplikasi ini menggunakan metode certainty factor implementasinya menggunakan bahasa pemprograman PHP dan penyimpanan data pendukungnya MySQL. Pada aplikasi ini akan ditampilkan gejala-gejala dari setiap penyakit. Hasil akhir aplikasi berupa jenis penyakit berdasarkan inputan gejala yang dipilih. Kata kunci : sistem pakar, penyakit Tyto Alba, certainty factor